2023
DOI: 10.1002/jlcr.4056
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence enhancement by deuterium

Crist N. Filer

Abstract: Created literally at the dawn of time, deuterium has been extremely valuable in so many chemistry roles. The subject of this review focuses on one deuterium application in particular: its enhancement of luminescence in many substances. After providing general overviews of both deuterium and luminescence, the early exploration of deuterium's effect on luminescence is described, followed by a number of specific topics. These sections include a discussion of deuterium‐influenced luminescence for dyes, proteins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…For a matter of comparison, the EuIDA 1 : 3 gel prepared in D 2 O instead of H 2 O presented a quantum efficiency of 76.51 %, calculated from its experimental luminescence data (Figure S9–S10). This large increase in η is caused by the lower vibrational frequencies of O−D bonds in comparison to O−H bonds, resulting in much less vibrational coupling with the Eu(III) excited state, which in turn, strongly minimizes A nrad [71] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a matter of comparison, the EuIDA 1 : 3 gel prepared in D 2 O instead of H 2 O presented a quantum efficiency of 76.51 %, calculated from its experimental luminescence data (Figure S9–S10). This large increase in η is caused by the lower vibrational frequencies of O−D bonds in comparison to O−H bonds, resulting in much less vibrational coupling with the Eu(III) excited state, which in turn, strongly minimizes A nrad [71] …”
Section: Resultsmentioning
confidence: 99%
“…This large increase in η is caused by the lower vibrational frequencies of OÀ D bonds in comparison to OÀ H bonds, resulting in much less vibrational coupling with the Eu(III) excited state, which in turn, strongly minimizes A nrad . [71] Another information that can be seen in Table 1 is the Judd-Ofelt intensity parameters Ω 2 and Ω 4 . For the EuIDA gel samples, increasing the ratio of IDA on the materials resulted in a decrease of Ω 2 and an increase of Ω 4 .…”
Section: Systemmentioning
confidence: 99%
“…It could be applied to enhance the pharmacological properties of bioactive molecules 5 and photophysics properties of fluorophores, 40−42 photoswitches, 43 and luminophores. 44 Trauner and co-workers 45 have confirmed that the activity of α7 nicotinic acetylcholine receptors (α7 nAChRs) could be regulated by photoligands. In this work, we developed a deuterated photoagonist and applied it to optically control the activity of α7 nAChRs in cells and behaviors of nematodes to investigate the effects of deuterium substitution on photophysical and photopharmacological properties of photoswitches.…”
mentioning
confidence: 96%
“…The deuterium strategy is a minor modification, which scarcely affects the molecular structure. It could be applied to enhance the pharmacological properties of bioactive molecules and photophysics properties of fluorophores, photoswitches, and luminophores . Trauner and co-workers have confirmed that the activity of α7 nicotinic acetylcholine receptors (α7 nAChRs) could be regulated by photoligands.…”
mentioning
confidence: 99%